Respuestas

2012-09-23T19:58:42+02:00
Monomios

axn + bxn = (a + b)bxn

axn − bxn = (a − b)bxn

axn · bxm = (a · b)bxn +m

axn : bxm = (a : b)bxn − m

(axn)m = amxn · m

 

Productos notables Binomios al cuadrado

(a + b)2 = a2 + 2 · a · b + b2

(a − b)2 = a2 − 2 · a · b + b2

Binomios al cubo

(a + b)3 = a3 + 3 · a2 · b + 3 · a · b2 + b3

(a − b)3 = a3 − 3 · a2 · b + 3 · a · b2 − b3

Binomio de Newton

Diferencia de cuadrados

a2 − b2 = (a + b) · (a − b)

Suma de cubos

a3 + b3 = (a + b) · (a2 − ab + b2)

2012-09-23T20:02:49+02:00

(X+Y)2=X2+2XY+Y2

(X-Y)2=X2-2XY+Y2

(X+Y)3=X3+Y3+3X*Y+3XY*

(X-Y)3=X3-Y3-3X*Y-3XY* (* AL CUADRADO)

(A+B+C)2=A2+B2+C2+2AB+2AC+ABC

A3+B3=(A+B)(A2-AB+B2)

A3+B3=(A-B)(A2+AB+B2)

(A+B)2+(A-B)2=2(A2+B2)

(A+B)2-(A-B)2=4AB

X+A)(X+B)=X2+(A+B)X+AB

(X-A)(X-B)=X2-(A+B)X+AB